2013
DOI: 10.1007/s00268-013-2093-7
|View full text |Cite
|
Sign up to set email alerts
|

Saucerization: A Modified Uncapitonnage Method of Surgery for Pulmonary Hydatidosis

Abstract: Our experience demonstrated a low complication rate associated with removing the thin margins of the residual cavity and changing the shape of it into a "saucer." The results were satisfactory and comparable to the results of other studies on pulmonary hydatid cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Hydatid disease is an important health issue in the World Health Organization’s (WHO) Eastern Mediterranean region countries [1]. Echinococcosis Gronulosis is the most common type of Echinococcosis in our endemic area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydatid disease is an important health issue in the World Health Organization’s (WHO) Eastern Mediterranean region countries [1]. Echinococcosis Gronulosis is the most common type of Echinococcosis in our endemic area.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary parenchyma involves the second common organ (lungs) after liver infection (10-30%). Due to the delay presentation of symptoms of pulmonary hydatid cyst, it can grow even in giant sizes [1-3]. …”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality rates are very low in adult patients. 1 3 The morbidity rate is higher in the case of giant lung cyst. 4 6 Prolonged air leak (10–19%), empyema (7%), pneumonia, and sterile air gap are some of the reasons of morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries are endemic, especially the Middle East, South America, and eastern and southeastern region of Turkey. 1 The lung and the liver are the commonly involved organs. We aimed to present this interesting case report because of the age of the patient and the diameter of the cyst.…”
mentioning
confidence: 99%
“…Hydatid cyst is an important health problem all over the world and the incidence in our country is 20 / 100.000 [6][7][8][9][10]. Lung is the most frequent location of the hydatid cysts at childhood period [10][11][12], and its reported that interestingly boys are effected more than girls.…”
Section: Discussionmentioning
confidence: 99%